2011
DOI: 10.1186/1741-7007-9-76
|View full text |Cite
|
Sign up to set email alerts
|

Following the genes: a framework for animal modeling of psychiatric disorders

Abstract: The number of individual cases of psychiatric disorders that can be ascribed to identified, rare, single mutations is increasing with great rapidity. Such mutations can be recapitulated in mice to generate animal models with direct etiological validity. Defining the underlying pathogenic mechanisms will require an experimental and theoretical framework to make the links from mutation to altered behavior in an animal or psychopathology in a human. Here, we discuss key elements of such a framework, including cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 181 publications
(186 reference statements)
0
12
0
Order By: Relevance
“…Our data adds to the recent and rapidly expanding use of model organism phenomics to discover the functions of poorly characterized genes identified through genomic sequencing. 44,101,[153][154][155][156][157][158] We have shown how such data can be used to identify novel genetic interactions, establish variant functional assays, and develop tests of phenotypic reversibility.…”
Section: Discussionmentioning
confidence: 99%
“…Our data adds to the recent and rapidly expanding use of model organism phenomics to discover the functions of poorly characterized genes identified through genomic sequencing. 44,101,[153][154][155][156][157][158] We have shown how such data can be used to identify novel genetic interactions, establish variant functional assays, and develop tests of phenotypic reversibility.…”
Section: Discussionmentioning
confidence: 99%
“…The use of animal models is a powerful tool in order to mechanistically understand neurodevelopmental disorders 18 in the context of rare genetic variants associated with complex traits 19 . The in vivo model used in the present study allowed us to identify an interesting pathophysiological process caused by the acute KD of Mcf2 in the developing mouse.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed a contribution of a combination of low-penetrance common DNA variants and more penetrant and damaging mutations in single genes or blocks of adjacent genes (copy number variants [CNVs]). An effective approach toward elucidating underlying disease mechanisms would be to focus on the human mutations with large effect sizes to generate transgenic animal models that bear the exact same mutation through advanced genetic engineering approaches (Arguello and Gogos 2012; Mitchell and others 2011) (see Box 1). However, only a few such mutations have been unequivocally identified (Marshall and others 2017; Singh and others 2016; Takata and others 2014).…”
Section: Modeling Schizophrenia In Animals: Emphasis On Cognitive Dysmentioning
confidence: 99%